Official Development Assistance (ODA) Jepang kepada Indonesia pada Masa Orde Baru (1966-1998) - Riyandewi, Desak Nyoman Risma; Wardoyo, Stedy (East Asian Review, 2024)
The History of Japan and Indonesia Relations: Japanese ODA to Indonesia during the New Order Era (1966-1998). Official Development Assistance (ODA) is a foreign aid used by the member nations of the Development Assistance Committee (DAC) in the Organization of Economic Cooperation and Development (OECD). ODA is used to contribute to the economic development and prosperity of developing countries. Japan as one of the DAC member countries provides ODA to said developing countries, with a special focus on the Asia region - Indonesia being one of the priority recipients. This research focuses on Japan’s ODA history, and the history of Japanese-Indonesian relations spanning the New Order era from 1966 to 1998. The methodology of research is qualitative, and based on historical data with the aim to explain Japan’s ODA strategies with regards to Indonesia as well as the reason behind it. The resources used to acquire data are primary sources from official websites of the Japanese Ministry of Foreign Affairs, and secondary sources such as books and journals describing Japan’s ODA to Indonesia. The findings of this research indicate the implementation of Japan’s ODA to Indonesia serves several national interests, as well as identifies interdependencies between the countries. Whereas Japan provides ODA to Indonesia with the goal of improving the country’s image on the world stage, as well as promoting mutual economic growth through investment and trade, Indonesia is also dependent on Japan’s ODA for economic growth and infrastructural development - in summary the welfare of the country. In summary both countries benefit from the ODA aid and have developed closer ties thanks to its continuation.